Do managers credibly use accruals to signal private information? Evidence from the pricing of discretionary accruals around stock splits - Louis, Henock; Robinson, Dahlia (Journal of Accounting and Economics, 2005)
Prior studies suggest that managers use their reporting discretion to signal private information. However, because managers are often assumed to use their discretion to mislead investors, discretionary accruals might be regarded as opportunistic. We posit that combining the accrual signal with other signals may be an effective means of communicating private information. One such signal is stock splits. The stock split signal lends credibility to the accrual signal whereas the accrual signal reinforces the split signal. Accordingly, we find that, at the split announcement, the market construes the pre-split abnormal accrual as a signal of managerial optimism rather than managerial opportunism.